2004
DOI: 10.1159/000078608
|View full text |Cite
|
Sign up to set email alerts
|

Asperger Syndrome, Obsessive-Compulsive Disorder, and Major Depression in a Patient with 45,X/46,XY Mosaicism

Abstract: Background: Although previous reports have described the association of autism, mental retardation, and schizophrenia with a missing Y chromosome, we are not aware of any case showing an association between this particular chromosomal abnormality and Asperger syndrome. Method: We report the case of a male patient with a combination of Asperger syndrome, obsessive-compulsive disorder and 45,X/46,XY mosaicism. During the follow-up, this individual has also developed a severe episode of major depression, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
1
6
1
1
Order By: Relevance
“…There have been at least eight other cases with similar karyotypes and behavioral–cognitive phenotypes that included intellectual disabilities and developmental delays [El Abd et al, 1999]. In another case report, a patient with Asperger syndrome, OCD and major depression was discovered to have 45X/46XY mosaicism [Fontenelle, Mendlowicz, Bezerra de Menezes, dos Santos Martins, & Versiani, 2004]. An earlier study [Telvi, Lebbar, Del Pino, Barbet, & Chaussain, 1999] reported that 2 (7%) patients were diagnosed with ASD in a sample of 27 patients with 45X/46XY mosaicism, but the nature and severity of OCB were not assessed.…”
Section: Structural Variant Disorders Associated With Both Asd and Ocbmentioning
confidence: 99%
“…There have been at least eight other cases with similar karyotypes and behavioral–cognitive phenotypes that included intellectual disabilities and developmental delays [El Abd et al, 1999]. In another case report, a patient with Asperger syndrome, OCD and major depression was discovered to have 45X/46XY mosaicism [Fontenelle, Mendlowicz, Bezerra de Menezes, dos Santos Martins, & Versiani, 2004]. An earlier study [Telvi, Lebbar, Del Pino, Barbet, & Chaussain, 1999] reported that 2 (7%) patients were diagnosed with ASD in a sample of 27 patients with 45X/46XY mosaicism, but the nature and severity of OCB were not assessed.…”
Section: Structural Variant Disorders Associated With Both Asd and Ocbmentioning
confidence: 99%
“…One case report describes a patient with AS, chromosomal aberration, and OCD who was successfully treated with ECT for a major depression, but it does not give specific information on how the OCD symptoms were influenced by ECT. 7 A retrospective study showed efficacy for OCD symptoms both in depressed and nondepressed patient groups. 2 There is also 1 case series report and several case reports on ECT for OCD with varying comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of ECT for the treatment of comorbid disorders in AS, there are only a few reports published and, to our knowledge, none that describes specific effect on OCD-like symptoms. 6,7 Here we present a successful case of ECT for prolonged and severely disabling obsessive-compulsive symptoms with hypochondriacal features in a patient with AS.…”
mentioning
confidence: 99%
“…Por outro lado, estudos sobre a ocorrência familiar do transtorno são praticamente inexistentes no país, assim como são escassas as pesquisas de cunho epidemiológi-co. Dessas últimas, apenas dois estudos epidemiológicos foram divulgados até o momento 33,34 . Já os trabalhos que focam outras áreas, como diagnóstico, marcadores neurogenéticos, aspectos psicossociais, entre outros, são mais frequentes 28,[35][36][37][38][39][40][41][42][43][44] . Assim, avaliações diagnósticas desse tipo, realizadas pelas equipes de saúde, poderiam ser ampliadas para familiares de primeiro grau.…”
unclassified